Total factor productivity of manufacturing sector in India: A regional analysis for the State of Haryana - Sehgal, Shallu; Sharma, Suparn (Economic Journal of Development Issues, 2012)
Using pooled data for the period of 1981-82 to 2007-08 for different categories of organized sector’s manufacturing industries for the sample state of Haryana, the present undertaking seeks to analyze the inter-temporal and inter-industry comparison of total factor productivity (TFP) measured by Malmquist productivity index (MPI), which is an application of DEA to panel data to calculate the indices of TFP change, technology change, efficiency change. The general development pattern observed by the Haryana is definitely not a healthy sign of structural change in the economy. The analysis of the discussion reflects that while the tertiary sectors have maintained its lion’s share in GDP of India and Haryana as well, the declining trend in the share of primary sector and more or less stable contribution of the secondary sector is noticeable. The study reveals that technical efficiency change is the key driver of TFPG in the manufacturing sector of Haryana during pre reforms period, however, the picture has turned around during the post reforms period. A positive impact of liberalization policy on technological advancement of the manufacturing sector of the state has been experienced. But, during the post reforms period the state has realized inefficiency in the utilization of resources in hand and it is really an alarming sign indicating that the incapability of manufacturing sector of the state in question to cope up with the technological advancement.DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7213 Economic Journal of Development Issues Vol.13 & 14 2011, pp.97-118